Transpalatine Route for the Correction of Transsphenoidal Encephalocele in a Child: A Case Report and Literature Review - Silva, Aldo José F. da; Lopes, Fabrício A. C. (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2017)
Introduction Transsphenoidal encephalocele is a rare neural tube defect characterized by the herniation of meninges and eventually of parts of the brain through a bony defect in the sphenoid bone. The clinical presentation is variable, and surgical treatment is controversial.Case Report This report describes the case of an 8-month-old female child diagnosed with transsphenoidal encephalocele. The child presented with obstruction of the upper airways and was fed via a nasogastric tube but did not present changes in the hypothalamic-pituitary-axis. The patient underwent surgery with the transsphenoidal–transpalatine route, with an excellent outcome and without fistulas or infections.Conclusions Although transsphenoidal encephalocele is a rare congenital anomaly, the transsphenoidal–transpalatine route for the correction of this type of encephalocele is a safe option and produces a favorable outcome in pediatric patients.
Keywords: encephalocele; transpalatine; transsphenoidal; meningoceles